An analysis on the effcetiveness of the role of parliament in strenghtening police accountability in Zimbabwe , 2013-2017. - Chirengendure, Gilbert (Midlands State University, 2020)
Police Accountability is critically important as it seeks to enhance a culture of police accountability and constitutionalism in Zimbabwe. This is very instructive in that it aptly recognises the instrumental role played by Parliament in cultivating the culture of accountable national governance systems in our national institutions such as the Police Service. As encapsulated in the Preambular statement of the Constitution of Zimbabwe, the people of Zimbabwe cherish “…freedom, equality, peace, justice, tolerance, prosperity and patriotism in search of new frontiers under a common destiny”.This reaserch is devided in to six chapters. In bringing up the information this paper will bring up the information on the problem .statement, . justification. of. the. study, research. methodologies. and the theoretical. and literature. review. of .the. study. This is the chapter introduction of the data of the entire exposition which is to be accomplished as the examination will be completed. his chapter reviews the Parliament and Police services in Africa, outlining its legal framework, its compositions and how they interact with each other. This chapter will also give references to other parliament and police services Africa, particularly South Africa, Namibia and Kenya showing how their Parliamentary committees executes their daily operations and ensure Police Accountability through the Parliamentary Democracy. It is in this context that this paper describes the historical background of Parliament of Zimbabwe, its structure, role and function from Rhodesian Parliament up to Zimbabwean Parliament and also Parliamentary Reforms in Zimbabwe in the 21st century taking a gander at the strategies and projects that has been started from 2000. This paper will be reviewing the role that can be played by Parliament of Zimbabwe to strengthen Police Accountability in Zimbabwe. Pointing out its oversight role, Law and policy making which act as guidelines to Police operations, Police budget Processes, Fiscal Management by the Parliament, Reports by Honorable Members through Motions and Questions in the Parliament. The last chapter will give the conclusions and recommendations on the study of the oversight role of the Parliament over the Police Services in Zimbabwe. It sought to identify the contributing factors inhibiting or enabling the smooth cooperation and coordination between Parliament and Police Services in Zimbabwe. Finally, recommendations thereof will be presented